A Novel Greedy Forwarding Mechanism Based on Density, Speed and Direction Parameters for Vanets - Bengag, Amina; Bengag, Asmae; Elboukhari, Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In the recent years, the study and developments of networks that do not depend on any pre-existing infrastructure have been very popular. Vehicular Ad Hoc Networks (VANETs) belong to the class of these networks, in which each vehicle participates in routing by transmitting data for other nodes (vehicles). Due to the characteristics of VANET (e.g. high dynamic topology, different communication environment, frequently link breakage…), the routing process still one of the most challenging aspects. Hence, many routing protocols have been suggested to overcome these challenges. Moreover, routing protocols based on the position of vehicles are the most popular and preferred class, thanks to its many advantages like the less control overhead and the scalability. However, this class suffer from some problems such as frequent link breakages caused by the high-mobility of vehicles, which cause a low PDR and throughput. In this investigation, we introduce a novel greedy forwarding strategy used to create a new routing protocol based on the position of vehicles, to reduce the link breakages and get a stable route that improves the PDR and throughput. The proposed Density and Velocity (Speed, Direction) Aware Greedy Perimeter Stateless Routing protocol (DVA-GPSR) is based on the suggested greedy forwarding technique that utilizes the density, the speed and the direction for selecting the most convenient relaying node candidate. The results of simulation prove that DVA-GPSR protocol outperforms the classical GPSR in all studied metrics like PDR, throughput, and the ratio of routing overhead by changing the quantity of vehicles in urban and highway scenarios.